Cutaneous presentation of chronic lymphocytic leukemia as unique extramedullar involvement in a patient with normal peripheral blood lymphocyte count (monoclonal B‐cell lymphocytosis). (3rd May 2013) - Tapia, Gustavo; Mate, José‐Luis; Fuente, María‐José; Navarro, José‐Tomás; Fernández‐Figueras, Maria‐Teresa; Juncà, Jordi; Ferrándiz, Carlos; Ariza, Aurelio
Abstract : Skin infiltration by chronic lymphocytic leukemia (CLL) is very rare and almost all reported cases occur in advanced stage. We report a patient with no relevant past medical history who presented with cutaneous erythematous plaques. A punch biopsy showed typical CLL morphologic and immunophenotypic features. Subsequent studies revealed a normal lymphocyte count in peripheral blood, and there was no evidence of lymphadenopathy or organomegaly. Flow cytometry demonstrated a clonal B‐cell population both in the bone marrow and peripheral blood (1.60 × 10 9 /l) with a CLL phenotype, but it did not fulfill required criteria for CLL diagnosis. Without cutaneous involvement, this case should be classified as monoclonal B‐cell lymphocytosis.